2021
DOI: 10.1155/2021/6675605
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Urban Metro Management Approach for Crowd Density Control

Abstract: Large crowding events in big cities pose great challenges to local governments since crowd disasters may occur when crowd density exceeds the safety threshold. We develop an optimization model to generate the emergent train stop-skipping schemes during large crowding events, which can postpone the arrival of crowds. A two-layer transportation network, which includes a pedestrian network and the urban metro network, is proposed to better simulate the crowd gathering process. Urban smartcard data is used to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The experiment results showed that the coefficients b 0 and b 1 of the TUD-population calibration method (Equation ( 2)) were 27,654 and 55. 4, respectively. The fitting results showed that the R-square of the regression equation was 0.76 (Figure 5).…”
Section: Tud-population Calibration Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The experiment results showed that the coefficients b 0 and b 1 of the TUD-population calibration method (Equation ( 2)) were 27,654 and 55. 4, respectively. The fitting results showed that the R-square of the regression equation was 0.76 (Figure 5).…”
Section: Tud-population Calibration Resultsmentioning
confidence: 97%
“…In open public spaces, which are open-boundary places, crowd accessing and leaving are unregulated, making them more likely to have large and risky crowd-gatherings compared to other places. Due to the high density of the crowd, once a crowd accident occurs, it will cause severe casualties [4][5][6]. For example, in the Love Parade accident of 2010 in Duisburg, Germany, 21 people died and more than 500 people were injured [7]; in the stampede that occurred in the Chenyi Square of Shanghai, 36 people died and 49 people were injured [8].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the present analysis primarily relies on daily-based data collection, thus limiting the provision of real-time prediction or early warning capabilities. However, integrating real-time data sources and applying predictive analytics could provide early warnings [15], [16], [18] and proactive management options [21], [22], [31]. This study has the potential to contribute to the development of ITS capable of managing the complexities of large-scale urban events.…”
Section: Discussionmentioning
confidence: 99%
“…For example, how many people use public transport (PT) to arrive at critical locations related with a special event could be used for PT operation planning. Hence, crowd management [5], [19] and evacuation design [20], [21], [22] could benefit from travel mode information concerning crowded events and special celebrations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works suggested that larger volume of trips can be attracted on the event day than on ordinary days [56]. Therefore, we define that the anomalous mobility fluxes are the large mobility fluxes which greatly exceed their ordinary values.…”
Section: Methodsmentioning
confidence: 99%